Effects of Neospora caninum infection on brain microvascular endothelial cells bioenergetics - Elsheikha, Hany M.; McKinlay, Charlotte L.; Elsaied, Nashwa A.; Smith, Paul A. (BioMed Central, 2013)
Background: The brain is the most commonly affected organ during Neospora caninum infection but the mechanisms utilized by this protozoan parasite for traversal of the blood–brain barrier (BBB) are not yet understood. Herein, we investigate the cellular pathogenicity of N. caninum infection on bioenergetics of human brain microvascular endothelial cells (HBMECs), a fundamental component of the BBB.